Ex Vivo Near-Infrared Molecular Imaging of Human Upper Urinary Tract Urothelial Carcinoma With a CD47-Based Targeted Tracer - Yan, Pengyu; Chen, Dan; Yan, Xutao; Yan, Xiaoting; Wang, Yingpeng; Liu, Chao; Yang, Xiaofeng (Frontiers in Oncology, 2022)
Objective The low detection rate of early and small tumors remains a clinical problem that urgently needs to be solved in the accurate diagnosis and treatment of upper urinary tract urothelial carcinoma (UTUC). The objective of this study is to evaluate the feasibility of CD47 as a target for optical molecular imaging of human UTUC and conduct preliminary ex vivo imaging experiments. Methods We firstly analyzed the genome-wide mRNA expression data from Gene Expression Omnibus (GEO). Paraffin-embedded tissue specimens comprising UTUC and normal urothelium were collected. All tissue specimens were used for immunohistochemistry to compare CD47 protein expression in normal and cancer tissue. Meanwhile, twelve patients undergoing radical nephroureterectomy were prospectively included in ex vivo imaging experiments. Freshly isolated upper urinary tract specimens were incubated with anti-CD47-Alexa Fluor 790, and then imaged under white light and near-infrared (NIR) light. Standard histopathologic evaluation was performed and findings were correlated with CD47-targeted NIR molecular imaging. Results The GEO data revealed that CD47 mRNA expression was higher in UTUC specimens than in paracancer normal tissue. In immunohistochemical analysis, the CD47 protein expression level was higher in both non-muscle-invasive and muscle-invasive (stage ≥ T2) UTUCs than in normal uroepithelium, and the localization of CD47 protein was the tumor cell membrane. In the ex vivo imaging experiments, all patients were pathologically diagnosed with UTUC and no adverse effects of anti-CD47-Alexa Fluor 790 on the histological structure of the tumor and normal uroepithelium were observed. In the NIR grayscale images, the mean fluorescence intensity of the tumor tissue was significantly higher than that of the adjacent normal background tissue, which greatly improved the visualization of the tumor. Conclusions CD47-targeted NIR molecular imaging could be a feasible and powerful strategy for the accurate diagnosis of UTUC. Larger scale randomized trials are needed.